RETHINKING CURRICULUM REFORM IN MADRASAH AND ‎PESANTREN: HILDA TABA’S MODEL AS A FRAMEWORK FOR ‎INTEGRATING ISLAMIC VALUES - Alfan Nawaziru Zahara; Mohammad Asrori; M. Mujab (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This article aims to analyze the relevance and potential application of Hilda Taba's curriculum development model in the reform of Islamic Religious Education (PAI) in madrasas, particularly through an integrated curriculum approach that emphasizes the linkage between Islamic values and 21st century learning needs. This research uses a qualitative method based on library research, by examining Hilda Taba's main works, national curriculum policy documents, and relevant academic literature in the field of Islamic education and curriculum development theory.The main focus of the study lies in a systematic examination of the core ideas of Taba, including the stages of need diagnosis, goal formulation, selection and organization of content, learning experience, and evaluation, and how these principles can be adapted in the context of madrasas.The results of the analysis show that the Taba model offers a participatory, reflective, and student-based curriculum approach. This approach is very suitable for the context of Islamic education in madrassas which have tended to follow a standard curriculum without adequate innovation space. By utilizing the Taba model, the PAI curriculum can be developed in a more contextual, integrative, and transformative manner that combines Islamic values with an active, collaborative, and character-oriented learning approach. In addition, this article also emphasizes the importance of the role of teachers as the main actors in curriculum development, as well as the need to change the evaluation paradigm in religious education from just cognitive measurement to assessment that includes affection and morality. These findings make a theoretical and practical contribution to the development of a responsive, relevant, and progressive Islamic curriculum, while strengthening the position of madrasas as educational institutions that are adaptive to changing times.